PHATIC EXPRESSIONS USED IN BUILDING A CONDUCIVE ATMOSPHERE AT PT BOSOWA BERLIAN MOTOR - Dwi Annisa; Fatimah Hidayahni Amin; Lely Novia (International Journal of Business English and Communication, 2025)
This research aims to find out what are the phatic expressions and the ways used by employees in using phatic expressions. This research uses a qualitative research design with a descriptive approach to describe the research subject. Data collection techniques used observation and audio recording and observation checklist. The result of this study shows that the use of phatic expressions in the office environment can create a conducive working environment. In this study, the employees used the types of phatic communication in three phases namely opening, medial, and closing phases. The phatic expressions are also adapted with three conditions, namely physical, psychological and security conditions. The ways they use communication are six ways namely greetings and small talk, expressing politeness and gratitude, acknowledging information, closing and farewells, team-building encouragement and expression of empathy. Using phatic expressions can establish good relationships between employees and can create a conducive work environment.